Welfare of animals in captivity: expose on diversity, enclosure size and enrichment, food and feeding regime in some zoos in south-west Nigeria (2021)
This study assessed the diversity of animals with respect to the number and sex, IUCN status, husbandry practices vis a vis enclosure size and enrichment, food and feeding regime in three zoos located in southwest Nigeria, in order to offer an insight into the welfare of animals in captivity in Nigerian Zoos, as well as the practice of captive breeding and/or conservation roles of modern zoos. Two of the five freedoms were focused on namely freedom from hunger and thirst and freedom to express most normal behaviour. It was revealed that a total of thirty-six species of animals (131 individuals) belonging to 25 families, 15 orders, and 3 classes (Aves, Reptiles and Mammals), were presented and displayed in the zoos. These animals largely belong to least concern conservation status of IUCN. Thirty species were without mates and some were housed with members of same sex. Animals’ enclosure sizes are designed to accommodate the needs of each species of animal; and enclosure enrichments were largely provided. The sizes of enclosures were however extremely smaller than the standard minimum enclosure requirements of animals in captivity. Feeding and feeding regime was done and appropriated with considerations to what obtains in their wild habitat and the digestive system of the animals. It was concluded that freedom from hunger and thirst was ensured in all the zoos given adequate food and feeding regime but hampered in terms of freedom to express most normal behaviour.